Hubungan Parasosial Komunitas Virtual Budaya Populer K-Pop dengan Calon Presiden Anies Baswedan - Adninta, Alya; Rusydi S, Banna; Falcao, Falcao; Amalia, Putri Chaerani (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
This research aims to understand the parasocial relationship between the virtual community of K-Pop fans and perceptions of presidential candidate Anies Baswedan through the social media platform X. The method used is netnography, which involves observation, downloading, and analyzing uploads on social media. Six procedural netnography movements are applied: initiation, investigation, immersion, interaction, integration, and incarnation. This research uses humanistic phenomenological, existential discourse, hermeneutic interpretation approaches, and thematic interpretation methods to explore themes that emerge from the data inductively. The research results show that parasocial relationships between the K-Pop fan community and Anies Baswedan can be formed and maintained through social media platforms such as @aniesbubble on X/Twitter. This supports the theory that mass and social media are important in forming parasocial relationships without requiring physical meetings. The findings show that interaction through social media content can create strong emotional bonds between fans and public figures. These findings indicate that the fandom phenomenon is not only limited to popular culture, but can also appear in a political context, and that support for Anies Baswedan via social media can impact people's political opinions.